Effect of the use dinoprost tromethamine on pregnancy rate in Mangalarga Marchador mares - Fonseca, Flávia Crespo Vieira de Leal; Jacob, Júlio César Ferraz; Sá, Marcus André Ferreira; Dutra, Gabriel Almeida; Guerson, Yuri Barbosa; de Jesus, Vera Lúcia Teixeira (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Fonseca F.C.V.L., Jacob J.C.F., Sá M.A.F., Dutra G.A., Guerson Y.B. & Jesus V.L.T. [Effect of the use dinoprost tromethamine on pregnancy rate in Mangalarga Marchador mares.] Efeito do uso de dinoprost trometamina sobre a taxa de gestação em éguas da raça Mangalarga Marchador. Revista Brasileira de Medicina Veterinária, 38(Supl.2):164-168, 2016. Departamento de Reprodução e Avaliação Animal, Universidade Federal Rural do Rio de Janeiro, BR 465, Km 7, Seropédica, RJ 23890-000, Brasil. E-mail: fvieira.vet@hotmail.com The aim of this study was to determine if the use of Dinoprost Tromethamine during diestrus affected the pregnancy rate in Mangalarga Marchador mares. A retrospective study through analyzing records of 173 Mangalarga Marchador mares totaling 669 estrous cycles. The data were separated into four groups: group I (n = 53 cycles): not submitted to hormonetherapy (control); Group II (n = 86 cycles): cycles submitted induction of ovulation using 1000 IU of hCG; Group III (n = 222 cycles): cycles submitted to oestrus induction with 5.0 mg of Dinoprost Tromethamine; Group IV (n = 308 cycles): estrus cycles induced with 5.0 mg Dinoprost tromethamine and ovulation induced using 1000 IU of hCG. Induction of ovulation occurs when the dominant follicle reached ≥ 35mm diameter. The use of PGF2a was from the seventh day after ovulation. Pregnancy diagnosis was performed 15 days after the ovulation detection in matrix mares. For embryo donors, was considered as a positive result the uterine washed resulting in embryo recovery. Was used the chi-square test (5% significance) and Fisher exact test, when recommended. The pregnancy rate obtained in the group I was 54.71% (29/53) in group II 59.3% (51/86) in group III 49.55% (110/222) and Group IV 59, 41% (183/308). There was no statistical difference (p = 0.132) for the pregnacy rate among the groups. Thus, use of Dinoprost Tromethamine in the seventh day after ovulation did not influence the pregnancy rate.